Evaluating the German Position Towards Asylum Seekers During the 2015 European Refugee Crisis - Muhammad Ahsan Jamal; Yue Xie (European Scientific Journal, ESJ, 2021)
The refugee crisis that emerged in 2015 was considered to be one of the worst political and humanitarian disasters and the huge influx of immigrants that arrived in Europe caused collective concerns among the receiving countries. The general attitude towards immigrants in Germany has been positive for years but the Syrian crisis prompted the German policies to become more lenient towards the refugees. Therefore, this paper analyzes Germany’s policy shift towards refugees after 2015 and examines the reasons behind the positive stance towards immigrants from the existing literature. The paper discusses the role of different factors ranging from economic, foreign policy considerations, ideological concerns to humanitarian values. In addition, this paper highlights the gaps in the literature and proposes directions for future research to comprehend German policies on immigrants. The research concludes with the findings that humanitarian values and past experiences have played a crucial role in shaping Germany’s refugee policy during the European refugee crisis.